SOCIAL ANXIETY IN PHYSICAL ACTIVITY PARTICIPATION IN PATIENTS WITH MENTAL ILLNESS: A CROSS‐SECTIONAL MULTICENTER STUDY. Issue 8 (26th March 2013) - De, Amber; Knapen, Jan; Vancampfort, Davy; De, Marc; Brunner, Emanuel; Probst, Michel
<x xml:space="preserve">Abstract</x> Background Social anxiety (SA) is a frequent comorbid condition in patients with mental illness. However, no data exist regarding SA in physical activity (PA) situations. The aim of the present study was to measure the level of self‐reported SA in PA participation in patients with mental illness compared to healthy controls. Methods Six hundred ninety‐three patients with mental illness and 2, 888 controls aged between 18 and 65 years completed the Physical Activity and Sport Anxiety Scale (PASAS). Group and gender differences in PASAS scores were tested by ANOVA and Scheffé's post hoc test. Results After controlling for gender (P < .05), the patient group (men 40.2 ± 14.4; women 49.2 ± 17) scored higher on the PASAS compared to control group (men 30.6 ± 12.2; women 37.3 ± 13.7). Within both groups, women reported higher levels of SA compared to men. Conclusions Our data indicate that patients with mental illness reported higher levels of SA in PA situations compared to healthy control subjects. Health professionals should consider SA when trying to improve outcome and adherence of patients with mental illness to PA interventions.